Increasing Motivation in Speaking Skill - Agustiawati, Hartini (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2021)
Abstract Motivation is needed in improving students’ speaking ability. It is so important to realize the strategy which is suitable to students’ life. Students face many problems in speaking English. They are afraid to talk and no self confidence to try speaking English. It is totally hard for students who learn English as a Foreign Language. They don’t have a place to practice their English. It makes students lazy to learn and speak English. In this case, teachers must be smart to find strategy or right technique. As a teacher or instructor of English, we must be active to find out appropriate strategy to help our students. In order to solve the problem, there will be some methods can be applied in teaching and learning process. These methods can motivate and inspire students to speak. Students will find ideas through the pictures, friends and condition around their class. They are so helpful and useful in order to improve students’ speaking ability. Key words: Motivation, Speaking